(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
: Foreign and domestic economists are devoted to improving the practice of financial support for entrepreneurial activity, and during the research, the significance, methods, and modern trends of financing business entities in a market economy were analyzed. The role of financial resources in the development of entrepreneurship, bank loans, state programs, and support mechanisms provided by international financial institutions have been studied in detail.